Forecast dominance testing via sign randomization - Ehm, Werner; Krüger, Fabian (Electronic journal of statistics, 2018)
We propose randomization tests of whether forecast 1 outperforms forecast 2 across a class of scoring functions. This hypothesis is of applied interest: While the prediction context often prescribes a certain class of scoring functions, it is typically hard to motivate a specific choice on statistical or substantive grounds. We investigate the asymptotic behavior of the test statistics under mild conditions, avoiding the need to assume particular dynamic properties of forecasts and realizations. The properties of the one-sided tests depend on a corresponding version of Anderson’s inequality, which we state as a conjecture of independent interest. Numerical experiments and a data example indicate that the tests have good size and power properties in practically relevant situations.
Gesehen am 12.07.2019